The development of a computer model for the replacement of dairy cattle in seasonally calving herds in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Veterinary Studies at Massey University - Crabb, Helen K. (Massey University, 1998)
A culling model for use in seasonally calving New Zealand dairy herds (CowCHOP) was developed. The model uses information retrieved from an on farm information system (DairyWIN) as well as farmer input to calculate an economic ranking of all animals within the dairy herd. This economic ranking is used to identify those animals that are most and least desirable for retention in the herd. Culling information was obtained from current Dairy MAN user herds. This information was analysed using survival analysis to determine the current removal risks of cattle from DairyMAN herds for inclusion in the model. Additional economic information was obtained from the literature and incorporated into the CowCHOP model. To understand removal risks and rates for culling, herd demographic data was analysis from a study on reproductive performance for the 1993/94 season. The study was limited to spring calving seasonal herds, typical of the New Zealand dairy industry. The New Zealand dairy industry is reliant on a largely pasture based production system which entails that herds calve annually during the spring months with a condensed calving pattern to optimise pasture utilisation. Cows are dried off in the late autumn for a dry period prior to the onset of calving the next season. This management system results in two periods of the season where cows are at greatest risk for removal, primarily early lactation and drying off.
Keywords: Dairy cattle, New Zealand; Calving; Calf culling